2018
DOI: 10.1016/j.fm.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavoring by non-conventional yeasts in sequential beer fermentations

Abstract: Non-conventional yeast species have great capacity for producing diverse flavor profiles in production of alcoholic beverages, but their potential for beer brewing, in particular in consecutive fermentations with Saccharomyces cerevisiae, has only poorly been explored. We have screened 17 non-conventional yeast species for production of an appealing profile of flavor esters and phenolics in the first phase of alcoholic fermentation, followed by inoculation with S. cerevisiae to complete the fermentation. For m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
30

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 51 publications
7
103
1
30
Order By: Relevance
“…Surprisingly, acetate esters, formed by the combination of acetate and higher alcohol (from amino acid catabolism), did not show any correlation with amino acid consumption or higher alcohols. Ester formation depends on the concentration of the co-substrates, acyl-CoA and alcohol, and the activity of the acyltransferases and esterases (24,46,47). Similar results were obtained by Gamero et al (23); the non-conventional yeast strains used in this study seem to resemble those of S. cerevisiae.…”
Section: Influence Of Amino Acid Consumption In Fermentation and Aromsupporting
confidence: 89%
“…Surprisingly, acetate esters, formed by the combination of acetate and higher alcohol (from amino acid catabolism), did not show any correlation with amino acid consumption or higher alcohols. Ester formation depends on the concentration of the co-substrates, acyl-CoA and alcohol, and the activity of the acyltransferases and esterases (24,46,47). Similar results were obtained by Gamero et al (23); the non-conventional yeast strains used in this study seem to resemble those of S. cerevisiae.…”
Section: Influence Of Amino Acid Consumption In Fermentation and Aromsupporting
confidence: 89%
“…Gibson et al () reported the use of Kazachstania servazzi and Naumovozyma dairenensis for enhancing the aroma profiles of lager beer (levels of 3‐methylbutanol, phenylethanol, and phenylethyl acetate as well as ethyl decanoate and caprylate were increased). Holt et al () found a strain of Pichia kluyveri with a high production of isoamyl acetate (over 80 mg/L after 2 days of fermentation) as an interesting candidate for sequential fermentation. T. delbrueckii strains have been proposed as bioflavouring agents, with significant changes, both increases and decreases, seen in the concentration of individual volatile flavour compounds when the yeasts are involved in cofermentation with production strains (Canonico, Agarbati, Comitini, & Ciani, ; Michel et al, ).…”
Section: Isolation and Brewing Potential Of Non‐saccharomyces Sppmentioning
confidence: 99%
“…In a study aimed at evaluating 17 non-conventional yeasts for the use as starter cultures in sequential beer fermentations with S. cerevisiae [40], P. kluyverii used as single starter culture produced isoamyl acetate and ethyl acetate in very high amounts, while high levels of ethyl acetate and low levels of isoamyl acetate were produced by P. anomala and P. kudriavzevii. When P. kluyverii was used in sequential fermentation with S. cerevisiae, inoculated 2 days after P. kluyverii with aim of completing the high-gravity beer fermentation, the total level of isoamyl acetate was much lower than expected.…”
Section: Non-conventional Yeasts For Bioflavoringmentioning
confidence: 99%